2022
DOI: 10.3390/jpm12101605
|View full text |Cite
|
Sign up to set email alerts
|

Radio-lncRNAs: Biological Function and Potential Use as Biomarkers for Personalized Oncology

Abstract: Long non-coding RNAs (lncRNAs) consist of at least 200 nucleotides. Although these molecules do not code proteins, they carry many regulatory functions in normal cells, as well as in cancer cells. For instance, many of these molecules have been previously correlated with tumorigenesis of different cancers and their reaction to various stress factors, such as radiotherapy, chemotherapy, or reactive oxygen species (ROS). The lncRNAs are associated not only with dysregulation in cancers after applied treatment bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 128 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…The development of new techniques, such as massive RNA sequencing, bioinformatics and even artificial intelligence (AI), caused an unbelievable growth in the number of discoveries of different types of ncRNA molecules [ 89 , 90 ]. The public release of data from the The Human Cancer Genome (TCGA) project made it possible to analyze the data in terms of searching for, for example, lncRNA, in 33 different cancers [ 91 , 92 ]. The TCGA is an immeasurable source of knowledge used as the first source of data for selection of genes and later validated in in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new techniques, such as massive RNA sequencing, bioinformatics and even artificial intelligence (AI), caused an unbelievable growth in the number of discoveries of different types of ncRNA molecules [ 89 , 90 ]. The public release of data from the The Human Cancer Genome (TCGA) project made it possible to analyze the data in terms of searching for, for example, lncRNA, in 33 different cancers [ 91 , 92 ]. The TCGA is an immeasurable source of knowledge used as the first source of data for selection of genes and later validated in in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs affect the radiation response of pancreatic cancer cells by regulating the expression of multiple genes and signaling pathways. [ 101 ] The expression of HOTAIR increased in pancreatic cancer cells, including PANC‐1 and AsPC‐1 cells, after radiation. Another study confirmed this finding by showing that HOTAIR knockdown heightened radiosensitivity and affected autophagy by increasing ATG7 expression.…”
Section: Lncrnas and Therapeutic Resistance In Pancreatic Cancermentioning
confidence: 99%
“…Emerging data highlight the significant role of lncRNAs in human pathologies ( 23 25 ), especially in malignant tumors ( 26 29 ). Dysregulation of lncRNAs has been closely linked to tumor growth, metastasis, and resistance to chemotherapy ( 30 34 ), radiotherapy ( 35 38 ), and immune responses ( 39 41 ), underscoring their crucial involvement in cancer development.…”
Section: Introductionmentioning
confidence: 99%